2008
DOI: 10.1002/0471142905.hg1705s56
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Inherited Disorders of Galactose Metabolism

Abstract: Galactose metabolism occurs through an evolutionarily conserved pathway in which galactose and uridine diphosphoglucose are converted to glucose-1-phosphate and uridine diphosphogalactose through the action of three sequential enzymes: galactokinase (GALK, EC 2.7.1.6), galactose-1-phosphate uridyltransferase (GALT, EC 2.7.7.12), and uridine phosphogalactose 4'-epimerase (GALE, EC 5.1.3.2). Inborn errors of galactose metabolism occur with impaired activity for each of the enzymes. Classical galactosemia is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Galactose in OXPHOSm must be phosphorylated by galactokinase 1, resulting in galactose-1-phosphate. Galactose-1- phosphate is then converted into glucose-1-phosphate by uridyl transferase, which uses UDP-glucose (Cuthbert et al, 2008). UDP-galactose-4-epimerase catalyzes the reversible conversion of UDP-galactose to UDP-glucose in galactose utilization metabolism (Cuthbert et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galactose in OXPHOSm must be phosphorylated by galactokinase 1, resulting in galactose-1-phosphate. Galactose-1- phosphate is then converted into glucose-1-phosphate by uridyl transferase, which uses UDP-glucose (Cuthbert et al, 2008). UDP-galactose-4-epimerase catalyzes the reversible conversion of UDP-galactose to UDP-glucose in galactose utilization metabolism (Cuthbert et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Galactose-1- phosphate is then converted into glucose-1-phosphate by uridyl transferase, which uses UDP-glucose (Cuthbert et al, 2008). UDP-galactose-4-epimerase catalyzes the reversible conversion of UDP-galactose to UDP-glucose in galactose utilization metabolism (Cuthbert et al, 2008). With this work, we demonstrated that the mitochondrial remodeling promoted by OXPHOSm in human skin fibroblasts increased UDP-galactose-4-epimerase (GALE) gene expression ( Figure 7G), possibly as an adaptive response due to the modified cell culture medium used.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of classical galactosemia usually involves the measurement of GALT enzyme activity in erythrocytes, and the enzyme activity is usually absent or barely detectable. Several fluorescent and radioactive enzyme assays for GALT have been described (411) since the causative enzyme defect was identified in 1956 in the Kalckar laboratory (12). Unfortunately, these assays are usually nonspecific and laborious, and do not demonstrate sufficient performance in measuring low enzyme activity (<5% of control values).…”
mentioning
confidence: 99%
“…For babies with positive screening results, i.e., increased galactose and/or galactose-1-phosphate, confirmatory analyses should follow. These should include quantitative enzyme assays from fresh whole blood, galactose-1-phosphate analysis in erythrocytes, and mutational analysis of galactokinase 1 (GALK1) 6 , UDP-galactose-4-epimerase (GALE), and galactose-1-phosphate uridylyltransferase (GALT) genes (7 ). Numerous disease-causing mutations have been identified, more than 200 mutations in GALT, 31 mutations in GALK1, and 20 mutations in GALE (8 ).…”
mentioning
confidence: 99%